EFEKTIVITAS HEALTH COACHING DALAM MENINGKATKAN KEPERCAYAAN DIRI AYAH MENJALANKAN TUGAS KESEHATAN KELUARGA - Amandus, Hieronimus; Halina, Rahayu; Nurbani, Nurbani; Roelanda, Alvi (Universitas Tribhuwana Tunggadewi, 2021)
Providing health coaching to family heads to become family health promoters can increase their self-esteem so that self-confidence will also increase. This study aims to determine the effect of health coaching on the self-confidence of the father figure as the head of the family in his readiness to carry out family health duties. This type of research is a quasi experimental pre and post test control group two groups in pairs. The sample size was 30 respondents in the treatment group and 30 respondents in the control group. taken using purposive sampling technique. Data were analyzed using paired t test and frequency distribution. Result shows mean of self-confidence the head of the family in the pre-test treatment group was 56.50 and post-test was 67.66 with mean difference between two groups was -11.16 and standard deviation was 8.87, while the mean of pre-test control group was 43 and post-test was 43.16, with mean difference between two groups being -0.16 and standard deviation was 4.25. In the treatment group the value of p α = 0.05, while in the control group the value of p α = 0.05. Providing health coaching on how to educate a father figure as the head of the family is proven to increase the confidence of the head of the family. Further research can be conducted to determine the effects of health promotion given by the father. ABSTRAK Memberikan health coaching kepada kepala keluarga untuk menjadi promotor kesehatan keluarga bisa meningkatkan harga diri mereka sehingga kepercayaan diri akan meningkat juga. Penelitian ini bertujuan untuk mengetahui pengaruh health coaching terhadap kepercayaan diri figure ayah sebagai kepala keluarga dalam kesiapannya menjalankan tugas kesehatan keluarga. Jenis penelitian quasi eksperimetal pre and post test control group dua kelompok berpasangan. Besar sampel 30 responden pada kelompok perlakuan dan 30 responden pada kelompok kontrol. yang diambil menggunakan teknik puposive sampling. Analisa data yang digunakan paired t test dan distribusi frekuensi. Hasil diproleh nilai rata-rata kepercayaan diri kepala keluarga kelompok perlakuan pre test adalah 56,50 dan post test adalah 67,66 dengan nilai selisih rata-rata kedua kelompok adalah -11,16 dan standar deviasi adalah 8,87, sedangkan nilai rata-rata kelompok kontrol pre test adalah 43 dan post test adalah 43,16 dengan nilai selisih rata-rata kedua kelompok adalah -0,16 dan standar deviasi adalah 4,25. Pada kelompok perlakuan p value α = 0.05, sedangkan kelompok kontrol p value α = 0.05. Memberikan health coaching tentang bagaimana cara melakukan edukasi kepada figure seorang ayah sebagai kepala keluarga terbukti dapat meningkatkan kepercayaan diri kepala keluarga. Penelitian lanjutan dapat dilakukan untuk mengetahui efek dari promosi kesehatan yang diberikan oleh ayah.